Students’ and Teachers’ Perceptions Toward the Implementation of Genre Based Approach on Students’ Writing Skill in Learning Procedure Text - Renita Donasari; Setian Aringga; Nur Afifi (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
In Merdeka Curriculum, Genre based approach becomes an approach that is required to be used by English teacher in teaching genre of text as stated in the regulation of Kemendikbudristek. By teaching and learning using genre based approach, teacher will teach and students will learn through four stages, Building Knowledge of Text (BKoF), Modelling of Text (MoT), Joint Construction of Text (JCoT), and Individual Construction of Text (ICoT). In English teaching, those stages are really useful in teaching English skills in learning various genre of text. This study aims to examine how students and teachers perceive the implementation of genre based approach on students’ writing skill in learning procedure text. This research used qualitative research methods with basic interpretative study as the research design. The research participants in this research were 2 English teachers and 60 students of 11th grade MA Al Mahrusiyah Lirboyo. However, the researcher took 30 students to be interviewed using FGD which the research participants were selected by using purposeful sampling. In collecting the data, researcher used questionnaire and interview. To analyze the data, the researcher used data reduction, data display, data verification and drawing conclusion method. To strengthen the credibility level of data collected, the researcher used trustworthiness of data which include of crediblity, transferability, dependability and confirmability. The results showed that in the implementation of genre based approach in the teaching and learning activities, students and teachers expressed positive perceptions by stating that this approach could help students in understanding the text because this approach contains of several stages.